Immune response, blood parameters and growth performance in broiler fed reduced protein diet supplemented with β-hydroxy-β-methyl butyrate and conjugated linoleic acid - Saki, Ali Asghar; Khoramabadi, Vahid; Nourian, Ali Reza; Zamani, Pouya (Acta Scientiarum. Animal Sciences, 2018)
In this experiment a total of 300 d-old broilers (Ross 308) were randomized across 20 floor pens and reared up to 42 d. Treatments includes: 1) A normal-protein diet (NPD) was formulated according to the Ross 308 recommendation (2014) by corn and soybean meal, 2) A reduced-protein diet (RPD) was prepared with dietary protein reduced by 12 g kg-1 (1.2%) relative to the NPD, 3) HMB+ RDP, 4) CLA+RDP and 5) CLA+ HMB+ RDP. The results showed that broilers fed HMB diet had higher Average Daily Gain (ADG) and Feed Conversion Rate (FCR) significantly improved by HMB during the grower or the whole period (p < 0.05). Titer of serum antibodies of Newcastle disease was maximum in treatment supplemented with CLA+HMB compared to the control (RPD) in day 42. In comparison with the control, feeding CLA increased Lymphocyte and decreased heterophil and H/ L ratio (p < 0.05). Insulin hormone secretion increased by dietary HMB (p < 0.05). Red Blood Cells (RBC) and Hemoglobin (Hb) was significantly increased by HMB supplemented diet (p < 0.05). It could be concluded that supplementations of HMB and CLA together in reduced-protein diet have positive effect on growth performance, immune system and hematological parameter.